2020
DOI: 10.1111/tmi.13395
|View full text |Cite
|
Sign up to set email alerts
|

Tropical pyomyositis: an update

Abstract: Tropical pyomyositis (TP) is a life-threatening bacterial infection of the skeletal muscle that occurs particularly among children, young adults and those with immunocompromised conditions. The appropriate diagnosis and treatment are often delayed due to its non-specific signs, leading to fatal consequences. Staphylococcus aureus, especially methicillin-susceptible S. aureus, is responsible for most TP cases. However, other bacteria (i.e. streptococci, Pseudomonas aeruginosa, Escherichia coli, Klebsiella spp.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…Panton–Valentine leukocidin is a pore-forming protein consisting of two sub-units (lukF-PV, lukS-PV) that target human granulocytes, monocytes, and macrophages ( Holzinger et al, 2012 ). It is mainly associated with skin and soft tissue infection (SSTI) ( Friesen et al, 2020 ), and in particular, pyomyositis in developing countries ( Shittu et al, 2020a ). This study identified PVL-positive MRSA from nine CCs in 10 countries.…”
Section: Discussionmentioning
confidence: 99%
“…Panton–Valentine leukocidin is a pore-forming protein consisting of two sub-units (lukF-PV, lukS-PV) that target human granulocytes, monocytes, and macrophages ( Holzinger et al, 2012 ). It is mainly associated with skin and soft tissue infection (SSTI) ( Friesen et al, 2020 ), and in particular, pyomyositis in developing countries ( Shittu et al, 2020a ). This study identified PVL-positive MRSA from nine CCs in 10 countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis is unclear, it seems that iron release from damaged muscle provides nutrients for the rapid growth of bacteria within the tissue. 9,10 It is not uncommon for patients to report strenuous exercise several hours or days before its onset. 11,12 The most frequently compromised muscles are in the lower extremities, especially the femoral quadriceps, iliopsoas and buttocks.…”
Section: Discussionmentioning
confidence: 99%
“…12 and 13). 22 The risk factors include diabetes, immunocompromised states, intravenous drug use, cellulitis and penetrating injuries. However patients with no significant history can also be affected, and there is a higher incidence among children and young adults.…”
Section: Infectionmentioning
confidence: 99%